Water Temperature Control System With PID Control Method and Fuzzy Logic Based on SCADA - sholeh, firma dilla; Suryatini, Fitria; Wisma Nugraha, Nur; Lilansa, Noval (Emitor: Jurnal Teknik Elektro, 2025)
The process of heating water to a certain temperature is commonly found in various industries, such as the chemical or food and beverage industries. This water heating is used to improve product quality, but temperature changes often become unstable due to external disturbances. Therefore, to ensure that the water temperature in the tank reaches the desired point with a fast and stable response, a PID controller or fuzzy logic controller is required. In water temperature control systems, the use of fuzzy logic in nonlinear systems is more effective than PID. Therefore, this study aims to compare the Ziegler-Nichols PID control method with the Sugeno fuzzy logic method to determine the appropriate and efficient control method. By examining the system stability and transient response of the water temperature controller as test parameters, it is hoped that the effects of these control methods will be beneficial for industrial implementation, thereby achieving good product quality based on SCADA Wonderware InTouch for monitoring, controlling, and modeling. The comparison between the Ziegler-Nichols PID and Sugeno Fuzzy Logic concludes that the use of Fuzzy Logic controllers has smaller error values and faster and more efficient system responses compared to PID in achieving the desired set temperature of 24 ºC in the experiment.